Floristic diversity in fire‐sensitive eucalypt woodlands shows a 'U'‐shaped relationship with time since fire. Issue 5 (19th July 2013) - Gosper, Carl R.; Yates, Colin J.; Prober, Suzanne M.
Summary: Understanding ecosystem responses to disturbance is important for effective management of biodiversity. Observed relationships between time since disturbance and diversity have taken a variety of forms, only some of which are explicitly predicted in models of vegetation succession. This makes generalization and predictions for specific communities difficult. Negative relationships have been the predominant diversity response to time since fire in fire‐prone Mediterranean‐climate ecosystems; however, few studies have analysed responses in infrequently burnt ecosystems such as Mediterranean‐climate woodlands dominated by fire‐sensitive trees. We used a space‐for‐time approach and multiple stand‐ageing techniques (Landsat imagery, growth ring counts and growth ring–size relationships) to characterize diversity and compositional changes with time since fire (3–370+ years) in fire‐sensitive Eucalyptus salubris woodlands in south‐western Australia. Species density and Pielou's evenness showed an overall 'U'‐shaped response to time since fire, although variability between plots was considerable. Plant functional type and species composition differed with time since fire, with greater richness and cover of ground layer, and 'long dispersal potential' functional types with increasing time since fire. Conversely, there was an early or intermediate peak in taller and 'short dispersal potential' functional types. We propose that the unusual 'U'‐shaped diversity–time since fire relationship is driven by competitively dominant tree and shrub layers having maximum cover at intermediate times since fire. Subdominant functional types were able to exploit lower levels of competition in the immediate post‐fire period and after density‐dependent thinning of the trees and shrubs. Synthesis and applications . Recurrent fire is not required to maintain diversity in these fire‐sensitive woodlands as diversity reached a maximum in mature vegetation. Fire intervals of < c . 200 years are likely to have adverse consequences on diversity, which is of conservation concern given apparently high recent rates of occurrence of fire. Changes in diversity were not apparent when times since fire were truncated to those available from remote sensing, illustrating that space‐for‐time studies defined solely by remote sensing may obscure equivalent 'U'‐shaped diversity–time since fire relationships. Abstract : Recurrent fire is not required to maintain diversity in these fire‐sensitive woodlands as diversity reached a maximum in mature vegetation. Fire intervals of < c . 200 years are likely to have adverse consequences on diversity, which is of conservation concern given apparently high recent rates of occurrence of fire. Changes in diversity were not apparent when times since fire were truncated to those available from remote sensing, illustrating that space‐for‐time studies defined solely by remote sensing may obscure equivalent 'U'‐shaped diversity–time since fire relationships.